Aerobic Exercise and Weight Loss Reduce Vascular Markers of Inflammation and Improve Insulin Sensitivity in Obese Women. Issue 4 (17th March 2014) - Ryan, Alice S.; Ge, Shealinna; Blumenthal, Jacob B.; Serra, Monica C.; Prior, Steven J.; Goldberg, Andrew P.
<x xml:space="preserve">Abstract</x> Objectives To examine the relationships between plasma and tissue markers of systemic and vascular inflammation and obesity and insulin resistance and determine the effects of aerobic exercise training plus weight loss (AEX+WL) and weight loss (WL) alone on these biomarkers. Design Prospective controlled study. Setting Veterans Affairs Medical Center and University research setting. Participants Overweight and obese sedentary postmenopausal women (N = 77). Interventions Six months, 3 d/wk AEX+WL (n = 37) or WL (n = 40). Measurements Total‐body dual‐energy X‐ray absorptiometry, abdominal computed tomography, hyperinsulinemic‐euglycemic clamps (a criterion standard method of assessing insulin sensitivity), adipose tissue biopsies (n = 28), and blood for homeostasis model assessment—insulin resistance, and soluble forms of intracellular adhesion molecule 1 (sICAM‐1) and vascular cell adhesion molecule 1 (sVCAM‐1), C‐reactive protein (CRP), and serum amyloid A (SAA). Results Body weight (P < .001), percentage of fat (P < .001), visceral fat (P < .005), triglyceride levels (P < .001), and systolic blood pressure decreased comparably after WL and AEX+WL (P = .04). Maximal oxygen consumption increased 16% after AEX+WL (P < .001). Insulin resistance decreased in both groups (P = .005). Glucose utilization according to the clamp increased 10% (P = .04) with AEX+WL and 8% with WL (P = .07). AEX+WL decreased CRP by 29% (P < .001) and WL by 21% (P = .02). SAA levels decreased twice as much after AEX+WL (−19%, P = .02) as after WL (−9%, P = .08). Plasma sICAM‐1 and sVCAM‐1 levels did not change, but women with the greatest reduction in plasma sICAM‐1 levels had the greatest reductions in fasting glucose (P = .02), insulin (P = .02), and insulin resistance (P = .004). Gluteal ICAM messenger ribonucleic acid levels decreased 27% after AEX+WL (P = .02) and did not change after WL. Conclusion Obesity and insulin resistance worsen markers of systemic and vascular inflammation. A reduction in plasma sICAM‐1 is important to improve insulin sensitivity. CRP, SAA, and tissue ICAM decrease with exercise and weight loss, suggesting that exercise training is a necessary component of lifestyle modification in obese postmenopausal women.